2017
DOI: 10.7150/jca.21218
|View full text |Cite
|
Sign up to set email alerts
|

Heteroplasmy and Copy Number Variations of Mitochondria in 88 Hepatocellular Carcinoma Individuals

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer mortality worldwide. In this study, we had analysed the copy number variations and heteroplasmic mutations of mitochondria (MT) in 88 HCC individuals. The average copy number of MT genome in normal samples was significantly greater than that in tumor samples. Overall, the number of heteroplasmic mutations in 88 tumor and their matched normal samples were 241 and 173, respectively. There was higher positive ratio of heteroplasmic mutations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In the individual heteroplasmy mean comparison, we observed that individual tumor samples presented almost 3-fold more heteroplasmic variants than internal control samples. A study conducted with patients of hepatocellular carcinoma also reported that tumor samples presented more heteroplasmic variants and a higher heteroplasmy ratio than their matched cancer-free samples 45 .…”
Section: Discussionmentioning
confidence: 95%
“…In the individual heteroplasmy mean comparison, we observed that individual tumor samples presented almost 3-fold more heteroplasmic variants than internal control samples. A study conducted with patients of hepatocellular carcinoma also reported that tumor samples presented more heteroplasmic variants and a higher heteroplasmy ratio than their matched cancer-free samples 45 .…”
Section: Discussionmentioning
confidence: 95%
“…MTND6 provides a quinone binding sites and is one of the six subunits ( ND1-ND6 ) of the complex I in electron transport chain (ETS) in mitochondria. Mutations in MTND6 are associated with an increase in metastatic potential that was associated with low NADH and high reactive oxygen species (ROS) in lung and breast cancer cell lines 65 , 66 and heptatocellular carcinoma 67 . Mutation in one of the subunits of ETS leads to low oxidative phosphorylation and increased glycolytic activity of mitochondria contributing to aggressiveness of childhood Acute Lymphoblastic Leukemia 68 .…”
Section: Discussionmentioning
confidence: 99%
“…The different expression of lncRNAs in colorectal cancer indicate that lncRNAs are involved in all stages of colorectal cancer. In colorectal cancer pathogenesis, lncRNAs are implicated in a variety of signaling pathways including the Wnt/-catenin signaling pathway, epidermal growth factor receptor (EGFR)/insulin-like growth factor type I receptor (IGF-IR) signaling pathway, KRAS and phosphatidylinositol-3-kinase (PI3K) pathways, transforming growth factor-beta (TGF-) signaling pathway, p53 signaling pathway, and the epithelial-mesenchymal transition (EMT) pathway 31 . While it is still unclear how STXBP5-AS1 contributes to colon carcinogenesis, in a study involving 1067 breast cancer samples, Guo et al identified STXBP5-AS1 among lncRNA genes which play a role in predicting the prognostic survival with good sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%